THE CONCENTRATION OF POTENTIALLY HAZARDOUS ELEMENTS AND YTTRIUM IN COAL FROM THE KARATAEVSKY MINE, IRKUTSK BASIN - E. A. Mikheeva (Geodinamika i Tektonofizika, 2022)
It is now known that coals throughout the world contain many valuable elements. In the Irkutsk Region, coal mining is provided by the resources of the Irkutsk coal-bearing basin. The Irkutsk basin is a large area of the Jurassic continental sedimentary deposits in the south of the Siberian craton, with the Cheremkhovo, Prisayan and Kuda formations. The upper Cheremkhovo formation is the primary coal-bearing formation of the Irkutsk basin. This paper presents the geochemical data on the Karataevsky coal mine. Trace element concentrations were obtained using X-ray fluorescence spectrometry. The average Th content (14.24 ppm) in the studied coal seam is higher than that in most of the world coals. The Co (35 ppm), F (1008 ppm), Sn (12 ppm), Th (34 ppm) concentrations in the coal shale consisting primarily of kaolinite (90 %) are higher than in ordinary coals. The coals should be used considering the concentrations of potentially hazardous elements that are high relative to the world coals. The studied coals can be interesting in terms of their slight enrichment in Y, with an average concentration of 19.7 ppm, which is 2.4 times higher than that in the world coal.